The 12th Century Church of the Sts. Boris and Gleb in Novogrudok: Certain Issues of the Decoration Remodeling - Jolshin, Denis D. (Actual Problems of Theory and History of Art, 2016)
The paper focuses on the research of remodeled decorative elements of the Church of the Sts. Boris and Gleb in Novogrudok. The research was based on the eld documentation revived and published 50 years after the archaeological excavations of the monument, as well as on the analysis of the archaeological collections of the building materials kept in Novgorod museum and the State Hermitage museum. Special features of the facades decor and glazed tiles floor pavement were also considered with the closest analogs pointed out in Polotsk and Grodno.
Keywords: Old Rus’ architecture; Byzantine architecture; plinth; brick; glazed tiles; floor pavement